Shapely bodies. The image of porcelain in eighteenth-century France - Jones, Christine A. (University of Delaware Press studies in 17th- and 18th- century art and culture., 2013)
This cultural history of porcelain-making in France tells the story of the politics behind the making of French porcelain's fashionable image.